L’Union du Maghreb ou l’invincible espoir - El Mehdi Lamrani (L’Année du Maghreb)
If international geopolitical and geo-economic change is to lead to a much-needed overhaul of cooperation in the Mediterranean, it is no less true that the prospect of an Arab Maghreb Union is an historical project and a beacon of hope for people. Thus, in the light of the Arab Spring, the crisis of European institutions and the emergence of the Union for the Mediterranean (UPM), we reflect on the importance and relevance of an Arab Maghreb Union. It remains an imperative of regional stability, which not only ensures economic prosperity and stability with its security implications for the Mediterranean north shore, but it represents a geopolitical pole contributing to the preservation of global equilibrium.